Limpograss: A Quick Reference - Yoana C. Newman (EDIS)
SS-AGR-302, a 3-page fact sheet by Yoana C. Newman, provides key data on this warm-season perennial grass used extensively for forage in south and central Florida, its origin, use, description, adaptation, management practices, fertilization, broad-leaf weed control, and pests and control. Includes references.  Published by the UF Department of Agronomy, March 2008.